Early intraocular pressure response following laser trabeculoplasty. Issue 10 (October 1985) - Frucht, J; Bishara, S; Ticho, U
Abstract : The early response in the intraocular pressure following laser trabeculoplasty was investigated in 38 patients. An increase in pressure was found in 16 patients (42%), of whom eight had a moderate (less than 9 mmHg) and eight a severe (greater than 10 mmHg) increase. The maximum increase was recorded during the first post-laser hour in 13 patients (34.2%) and at 4 h in three patients postoperatively. A routine follow-up observation at 4 h after laser treatment is recommended to prevent 'silent' hypertensive risk.